PERAN KELOMPOK WANITA TANI DALAM PEMANFAATAN PEKARANGAN PANGAN LESTARI (P2L) DI DESA GIRIMUKTI KECAMATAN SAGULING - Nur Lailatul Qodariah; Firdaus, Nunu Mahmud; Mulyono, Dinno (IKIP Siliwangi, 2024)
This study aims to analyze the role of women farmer groups in the utilization of the Sustainable Food Yard Program or P2L. Sustainable Food Yard or P2L is a joint activity carried out by community groups to make yard land a permanent or sustainable food source. Utilization of Sustainable Food Yard in Girimukti Village is still said to be not optimal, so it is necessary to increase the Utilization of Sustainable Food Yard Program with the role of Women Farmers Group in Girimukti Village. In this study, researchers used descriptive qualitative research, in collecting data researchers used observation techniques, documentation and interviews with a sample of 3 people who were part of the farm women's group. The results of this study indicate that the role of the farm women's group is in the high and good category. Strategies in an effort to increase the role of farmer groups as a place of learning by conducting counseling and conducting pilot plots.